(untitled) (Proceedings of International Educators Conference, 2022)
In this article, sources related to cattle breeding in Turkestan in the late XIX - early XX centuries were researched and these sources were comparatively analyzed. The author emphasizes that archival documents, periodical press materials and statistical data are of great importance in the study of livestock industry.